Untethered miniature robots for minimally invasive thrombus treatment: From bench to clinical trials - Qinglong Wang; Fangling Zhao; Ben Wang; Kai Fung Chan; Bonaventure Yiu Ming Ip; Thomas Wai Hong Leung; Xin Song; Li Zhang; Jue Xie (The Innovation)
Untethered miniature robots (MRs) offer a minimally invasive way to address adverse vascular blockages, such as cerebrovascular thromboembolism, myocardial infarction, and pulmonary embolism. This review explores three key questions: what are the design principles of MRs from both engineering and clinical perspectives? How can visible intervention of MRs in three-dimensional (3D) branched vessels be achieved? What is the clinical procedure for treating thrombus using designed MRs? Recent progress in MRs for thrombus removal is summarized, and, more importantly, the pros and cons of MRs are discussed. We also evaluate the challenges that may hinder their clinical deployment and propose future research directions, bridging the gap between the bench and the bedside. Public summary: • Ischemic stroke is a leading cause of death, with thrombectomy and thrombolysis being common treatments. • Limited catheter accessibility and the serious side effects of thrombolytic drugs are the main challenges. • Untethered miniature robots (MRs) enable precise therapy with minimized side effects. • This work explores the design principles, current challenges, and prospects of MRs for thrombus treatment.